1961
DOI: 10.1021/jo01060a003
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of N-Substituted Isomaleimides

Abstract: Reaction of terephthalamie acid with ethyl chloroformate and triethylamine. A solution of terephthalamie acid (1.4 g., 0.0085 mole) and triethylamine (1.72 g., 0.017 mole) in 20 ml. of dichloromethane was cooled to 0-6°and 1.9 g. (0.018 mole) of ethyl chloroformate was added. Stirring was continued for 3.5 hr. at room temperature after the addition. The mixture was filtered to remove triethylamine hydrochloride and the solvent was removed under reduced pressure. The residue was washed several times with ether.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

1971
1971
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 0 publications
0
42
0
6
Order By: Relevance
“…Six RIMI were prepared from maleic anhydride and the corresponding primary amines, according to the method by Cotter et al 5 Boiling points and melting points of RIMI are as follows: nBIMI bp 96°Cj6 mmHg, iBIMI bp 97°Cjl7mmHg, tBIMI bp 32-36°Cj5.0 x 10-2 mmHg, CHIMI bp 76--79°Cj5.0x 10-2 mmHg; mp 35-37°C, PhiMI mp 62-63°C, and MBZIMI bp 112-ll4°Cj5.0x 10-2 mmHg. RIMI monomers were identified by IR and NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Six RIMI were prepared from maleic anhydride and the corresponding primary amines, according to the method by Cotter et al 5 Boiling points and melting points of RIMI are as follows: nBIMI bp 96°Cj6 mmHg, iBIMI bp 97°Cjl7mmHg, tBIMI bp 32-36°Cj5.0 x 10-2 mmHg, CHIMI bp 76--79°Cj5.0x 10-2 mmHg; mp 35-37°C, PhiMI mp 62-63°C, and MBZIMI bp 112-ll4°Cj5.0x 10-2 mmHg. RIMI monomers were identified by IR and NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…12 types of RIMI were synthesized according to the method by Cotter et al, 13 as shown in Scheme 1. N-Substituted maleamic acid CHCO,11 o + CHCO,,, the results of elemental analysis, IR and 1 H NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…This methane dianilinebismaleamic acid (0.05 mol) was treated with DCC (0.1 mol) in dichloromethane and an ether mixture. 13 The precipitated dicyclohexylurea was filtered off and the product MBIMI was recovered from the filtrate by removing the solvent under reduced pressure. MBIMI, after recrystallization from benzene-ether, melted at 155oC.…”
Section: Mbimimentioning
confidence: 99%